2021
DOI: 10.1177/00333549211006973
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Case Surveillance: Trends in Person-Level Case Data Completeness, United States, April 5–September 30, 2020

Abstract: Objectives To obtain timely and detailed data on COVID-19 cases in the United States, the Centers for Disease Control and Prevention (CDC) uses 2 data sources: (1) aggregate counts for daily situational awareness and (2) person-level data for each case (case surveillance). The objective of this study was to describe the sensitivity of case ascertainment and the completeness of person-level data received by CDC through national COVID-19 case surveillance. Methods We compared case and death counts from case surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 17 publications
0
13
2
1
Order By: Relevance
“…The COVID-19 (Coronavirus Disease 2019) Pandemic caused by SARS-CoV2 (severe acute respiratory syndrome coronavirus 2) has upended the global community, infecting over 300 million people and claiming over 5 million lives in its wake (Coronavirus Disease (COVID-19) Situation Reports n.d. ). In case surveillance data from the Centers for Disease Control and Prevention (CDC) during January to May of 2020, 14% of patients were hospitalized, 2% required ICU (intensive care unit) admission and 5% died (Gold et al 2021 ). In the USA case surveillance reports from 2020, during the time our data was collected, found that 14% of patients required hospitalization, 2% required ICU admission and 5% of all patients died (Gold et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The COVID-19 (Coronavirus Disease 2019) Pandemic caused by SARS-CoV2 (severe acute respiratory syndrome coronavirus 2) has upended the global community, infecting over 300 million people and claiming over 5 million lives in its wake (Coronavirus Disease (COVID-19) Situation Reports n.d. ). In case surveillance data from the Centers for Disease Control and Prevention (CDC) during January to May of 2020, 14% of patients were hospitalized, 2% required ICU (intensive care unit) admission and 5% died (Gold et al 2021 ). In the USA case surveillance reports from 2020, during the time our data was collected, found that 14% of patients required hospitalization, 2% required ICU admission and 5% of all patients died (Gold et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In case surveillance data from the Centers for Disease Control and Prevention (CDC) during January to May of 2020, 14% of patients were hospitalized, 2% required ICU (intensive care unit) admission and 5% died (Gold et al 2021 ). In the USA case surveillance reports from 2020, during the time our data was collected, found that 14% of patients required hospitalization, 2% required ICU admission and 5% of all patients died (Gold et al 2021 ). While several studies have reported the detrimental effects of tobacco smoking on outcomes in patients with COVID-19(Saadatian-Elahi et al 2021 ; Patanavanich and Glantz 2020 ), little is known about these outcomes in people who use cannabis products.…”
Section: Introductionmentioning
confidence: 99%
“…The degree of underestimation is likely increasing with time 4 . A few studies have examined the performance of case-based passive surveillance for SARS-CoV- 2 14,15 but a broader evaluation of SARS-CoV-2 surveillance systems in relation to current public health goals 16 is important.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of underestimation is likely increasing with time 4 . A few studies have examined the performance of case-based passive surveillance for SARS-CoV-2 14,15 but a broader evaluation of SARS-CoV-2 surveillance systems in relation to current public health goals 16 is important. Similar to prior findings using the same methodology 17,18 , we estimated a higher prevalence of SARS-CoV-2 infection among those who were vaccinated and boosted compared with those who were fully vaccinated but not boosted and those who were unvaccinated.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, incompleteness of reporting has been frequently found when assessing the data quality of health information databases before the COVID-19 pandemic [24] and associated with the surveillance of COVID-19 cases in Portugal [25] or in other countries. [26] , [27] It is widely known that high-quality data is the basis for decision making guidance, especially during a crisis such as a pandemic. [28] However, the priority of public health doctors is to track and isolate their contacts, and, in this way, the surveillance data can be collected in haste.…”
Section: Discussionmentioning
confidence: 99%